2020
DOI: 10.1016/j.eururo.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Molecular Classification of Muscle-invasive Bladder Cancer

Abstract: Background: Muscle-invasive bladder cancer (MIBC) is a molecularly diverse disease with heterogeneous clinical outcomes. Several molecular classifications have been proposed, but the diversity of their subtype sets impedes their clinical application. Objective: To achieve an international consensus on MIBC molecular subtypes that reconciles the published classification schemes. Design, setting, and participants: We used 1750 MIBC transcriptom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
899
5
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 838 publications
(1,030 citation statements)
references
References 42 publications
27
899
5
7
Order By: Relevance
“…The vast majority (IHC: 92% and mRNA: 87%) of this cohort was classified as "luminal-like" subtypes Uro or GU, which in more advanced stages make up only about 50%. 28,30,44 The dynamics of molecular subtypes in the cohort was interesting: Patients that progressed with the Uro subtype tended to have only prior Uro tumors; patients that progressed with the GU subtype, tended to have either Uro or GU prior tumors; and patient that progressed with nonluminal subtypes had few prior tumors that could be of any subtype. These data explain to some degree why certain subtypes are more frequent at different disease stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority (IHC: 92% and mRNA: 87%) of this cohort was classified as "luminal-like" subtypes Uro or GU, which in more advanced stages make up only about 50%. 28,30,44 The dynamics of molecular subtypes in the cohort was interesting: Patients that progressed with the Uro subtype tended to have only prior Uro tumors; patients that progressed with the GU subtype, tended to have either Uro or GU prior tumors; and patient that progressed with nonluminal subtypes had few prior tumors that could be of any subtype. These data explain to some degree why certain subtypes are more frequent at different disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus molecular subtypes of MIBC were also applied. 30 Molecular classification results are available in Supporting Information Table S1.…”
Section: Transcriptomics and Rna-based Molecular Subtype Classificationmentioning
confidence: 99%
“…1); but since then, one has been developed and will be reported soon. 30 However, meta-analyses showed that the different subtyping methods all shared dichotomization "basal" and "luminal" at the highest level. 31,32 Furthermore, the basal subtype was always characterized by high expression of KRT5/6 and KRT14, and low/undetectable expression of FOXA1 and GATA3, whereas the luminal subtypes were enriched with biomarkers characteristic of urothelial differentiation.…”
Section: Predictive Biomarkers For Cddp-based Chemotherapy In Advancementioning
confidence: 99%
“…6 Recently, a consensus was reached for the molecular classification of MIBC identifying six subtypes with distinct histological, molecular and clinical characteristics. 7 Molecular subtypes of the NMIBC are less studied. Classification of NMIBC based on RNA-sequencing 8 supports the existence of three subclasses, including a luminal/well-differentiated (Class 1), a basal-like (Class 3) and a luminal/carcinoma in situ (CIS)-like subtype (Class 2), the latter associated with worse outcome in comparison to the two former (UROMOL cohort).…”
Section: Introductionmentioning
confidence: 99%